Developing a Customized Indoor Air Quality Control Parameters for a Precision Machining Lab (Case Study: FabLab at President University) - Keisha Fawwaaz; Yosef Barita Sar Manik (Jurnal Serambi Engineering, 2026)
The indoor air quality (IAQ) issues in engineering educational laboratories arise from high equipment usage, material handling, and continuous student presence. Equipment and processes at engineering laboratories have the potential in generating pollutants that may threaten health and safety and therefore, continuous monitoring and evaluation is essential. This study developed a customized framework for indoor air quality (IAQ) management for the engineering laboratories at President University focusing on Precision Laboratory comprising machining, CNC operations, and concrete 3d printing. Two national regulations, Permenkes No. 2/2023 and Permenaker No. 5/2018, were evaluated and mapped with the associated risks arising from relevant laboratory activities, and strictness of threshold limits to ensure comprehensive and protective assessment. As a result, ten key IAQ parameters were identified: temperature, relative humidity, air velocity, noise level, PM2.5, PM10, TSP, carbon dioxide (CO₂), carbon monoxide (CO), and volatile organic compounds (VOC) as critical parameters for digital manufacturing lab. These parameters represent thermal comfort, biological, physical, and chemical hazards from overall laboratory processes and human occupancy. The systematic IAQ parameter framework developed from this study serves as a benchmark for educational engineering laboratories nationwide in operationalizing the compatibility with Indonesian engineering higher education accreditation requirements.